2003
DOI: 10.1097/01.blo.0000063602.67412.83
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Adipogenesis in Bone and Marrow: A Possible Mechanism for Osteonecrosis

Abstract: The effect of alcohol on rabbit bone marrow and on the differentiation of mouse bone marrow stromal cells was investigated. Alcohol was administered intragastrically at a dose of 10 mL/kg/day for 1 to 6 months. Alcohol induced a significant increase in serum lipid peroxides, triglyceride, and cholesterol, and a reduction in superoxide dismutase activity. Fatty infiltration in the liver and adipogenesis in bone marrow were found histologically after alcohol administration. Fat cell hypertrophy and proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 15 publications
2
140
1
7
Order By: Relevance
“…Quantitative analysis of the mRNA levels by real-time RT-PCR method revealed that Osf2/Cbfa1, the marker gene for osteogenesis in the PPARγ-siRNA group, was up-regulated by 17.4% compared to the adipogenic control group (P= 0.000), and almost reached the gene level of cells cultured in pure osteogenic medium without alcohol (P=0.302).…”
Section: Gene Expression and Protein Synthesis For Osteogenic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative analysis of the mRNA levels by real-time RT-PCR method revealed that Osf2/Cbfa1, the marker gene for osteogenesis in the PPARγ-siRNA group, was up-regulated by 17.4% compared to the adipogenic control group (P= 0.000), and almost reached the gene level of cells cultured in pure osteogenic medium without alcohol (P=0.302).…”
Section: Gene Expression and Protein Synthesis For Osteogenic Markersmentioning
confidence: 99%
“…Several's studies [15][16][17] have provided evidence that alcohol shifts lineage commitment and differentiation of MSCs from osteogenesis to adipogenesis by upregulation of gene expression for peroxisome proliferator-activated receptor gamma (PPARγ); however, the molecular mechanism underlying the reciprocal relationship is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…For alcohol-induced ONFH to develop in adults, the total alcohol exposure threshold needs to be approximately 150 L of 100% ethanol, which corresponds to a consumption of 400 mL or more of absolute ethanol per week [23]. We determined the weekly alcohol consumption by summing the ethanol contents of beverage types consumed over a typical week.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that alcohol contributes to abnormal lipid metabolism in the stromal cells of bone marrow, decreasing osteogenesis while enhancing adipogenesis. This abnormal metabolism produces intracellular lipid deposits resulting in the death of osteocytes, which may be associated with the development of ON [12]. The adipogenesis may also pack the marrow, thereby increasing the intraosseous pressure and negatively affecting the bone microcirculation.…”
Section: Alcoholmentioning
confidence: 99%